(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
In this paper, from the literature of Luis Vidales’s Suenan timbres, we explore the dynamics of Colombian rising cities that initiate an accelerated modernization process, deprived of an appropriate development of modern thinking, along with the new material advances, which makes it impossible to debate the relevance and the process followed by these types of transformations. This situation leads Colombia to experience the idiotism of modernization without modernity, impeding men to understand the needs and conflicts generated by progress. These villages from twentieth century beginnings quickly turn into city projects determined by the arrival of new objects, creating a mobile and noisy atmosphere, opposed to villages’ passivity. From poetics committed to social and political change, Vidales recreates reality as a poet of criticism in Colombia.